The use of CytoSorb hemoadsorption in critically ill patients: a narrative review - Lei, Kaixin; Chen, Ao; An, Xinqi; Guo, Jun; Su, Baihai; Li, Yupei (Frontiers in Medicine, 2025)
Inflammation, a complex biological response against injury or infection, is an important pathological basis for various critical diseases. A “normal” immune response exemplifies a balanced dialogue between immunological cells and a medley of pro- and anti-inflammatory mediators. However, under pathological conditions, this equilibrium is disrupted by the overwhelming release of cytokines, also known as a cytokine storm, which significantly contributes to multiple organ dysfunction and death. Accumulating clinical evidence highlights the efficacy of CytoSorb® hemoadsorption in eliminating damage-associated molecular patterns, pathogen-associated molecular patterns and excessive cytokines from the blood, which underscores the broad use of CytoSorb® in managing various critical conditions. In this narrative review, we conduct a state-of-the-art review of CytoSorb® hemoadsorption in daily critical care practice. By searching ‘CytoSorb®’, ‘cytokine absorption’, ‘hemoadsorption’ and ‘hemoperfusion’ in PubMed, Embase and Web of Science, we discussed the rationale and research progress for cytokine adsorption with CytoSorb® from January 2019 to May 2025. Then, we summarize the latest clinical evidence regarding the use of CytoSorb® in sepsis, cardiac surgery, extracorporeal membrane oxygenation, hepatic diseases, rhabdomyolysis and burn injuries. Finally, we elaborated on the impact of CytoSorb® on the clearance rates of antibiotics and anticoagulants to address its safety concerns and highlighted ongoing debates on the timing, dose and patient selection criteria of CytoSorb® hemoadsorption, which requires future research to optimize actual benefits.